Investigation of Control Method for Connected-Automated Vehicle to Multiplex Dedicated Bus Lane - Wei-Jie Xiu; Li Wang; Meng-Yang Guo; Li-Li Zhang; Qi Zhao (Journal of Advanced Transportation)
Dedicated bus lanes (DBLs) have been widely utilized to ensure public transport priority. To improve overall road efficiency, various control methods of multiplexing DBL are developed and discussed. In this study, we focus on the control method which is based on the connected-automated vehicle (CAV) technology, and the proposed method is validated by using microscopic traffic simulation. The simulation results show that two proposed control methods of multiplexing DBL can reduce the average delay and the average number of stops and increase the travel speed. In comparison, the real-time control method based on the CAV technology offers better effects than the improved signal light control method.